(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The article discusses legal regulations in the field of advocate’s secret many European countries as well as in the USA and Canada. An obligation to keep advocate’s secret as a professional duty of an advocate and consequences of this duty in the field of criminal proceeding were discussed. In particular; the author discusses the problem off hearing an advocate as a witness or accused when deposition or explanations refer to circumstances coming within advocate’s secret. The problems of admissibility of searching advocate’s premises, control of correspondence and telephone calls of an advocate with his client were also dealt with.